Kajian Kinerja Pelayanan General Cargo Terminal Jamrud Di Pelabuhan Tanjung Perak Surabaya - Ayu Fajar Ulfany; Achmad Wicaksono; M. Ruslin Anwar (Rekayasa Sipil, 2017)
Terminal Jamrud is a busy terminal among three others terminals run by PT. Pelabuhan Indonesia III branch of Tanjung Perak that serving general goods cargoes and dry bulk both dosmetically and internationally. The source of the problem to increase terminal performance are capacity building, efficiency, productivity and environment. The objectives of this study were to identify the existing performance of loading and unloading of general cargo and to arrange strategies for the development of Terminal Jamrud at Tanjung Perak Port using SWOT analysis. Based on secondary data: 1) the best operational performance of service is the productivity of loading and unloading of general cargo, 2) the best performance is the approach time (AT), 3) the waiting time (TW) has not fulfilled the expected achievement as it is stil below the standard, 4) attributes of utility services, non-container terminal dock facilities, SOR and YOR still needs to be improved. The development strategies of Terminal Jamrud at kuadran I i.e grapid rowth strategy.